Hubungan Pola Konsumsi Ikan Terhadap Kadar Kolesterol Pada Lansia Di Posyandu Aisyiyah Cabang Solo Utara Ranting Banyuanyar - Anggarianti, Aurulia Banuar (2016)
Background : Fish consumption may degrade cholesterol plasma. The research has shown that consumption 1 time/week as much as 100 grams can decrease cholesterol plasma. Objective : The present study aimed to assess the relationship between the consumption of fish including type, number,and frequency with cholesterol levels in elderly. Research Methods : a cross sectional study was conducted in a consecutive sampling of 42 elderly aged 46-75 years in Posyandu Aisyiyah Cabang Solo Utara Ranting Banyuanyar. An average of semi quantitative food frequency questionnaire to obtain consumption of fish . Plasma cholesterol was taken using electrode-based biosensor method. Results : of 42 participants 34 (80,95%) participants was fish eater and 8 (19,06%) participants was non fish eater. Thirty four participants which is fish eater 22 (64,7%) participants was consumption non oily fish, average of fish consumption(median ± IQR) 8,23 ± 11,46, frequency of fish consumption (median ± IQR) 2,5 ± 5,25 and plasma cholesterol (median ± IQR) 247 ± 47. There was no relationship between fish type with plasma cholesterol (p=1,00), no relationship between number of fish consumption with plasma cholesterol (p=0,060) as well as frequency fish consumption with plasma cholesterol (p=0,201). Conclusions : consumption of fish appropriate not always adequately impact to cholesterol plasma in elderly at Posyandu Lansia Aisyiyah Cabang Solo Utara Ranting Banyuanyar. Keywords : Fish Consumption, oily fish, non oily fish, total cholesterol level Bibliography : 47 (1982 - 2013)